Palestinian NGOs: External Governance, Stakeholders, and Accountability - Awashreh, Raed (Universitas Muhammadiyah Yogyakarta, 2018)
This article addresses nongovernment organizations (NGOs) accountability, relationship with stakeholders, and what kind of mechanisms - tools or processes have NGOs put in place to ensure all types of accountabilities. The assumption in this study is that Palestinian NGOs, individually and collectively, are more accountable to their donors and to the Palestinian Authority to a lesser extent as NGOs need these two which are the only stakeholders with a real power to exercise on the NGOs and enforce their accountability requirements. The research argues that stakeholdersâ power is therefore determining NGO accountability. The findings highlighted the failure of NGOs in meeting the most pressing needs of the public and the poor in particular. The upward-accountability also signals of the sectorâs inability to consolidate its legitimacy or define an agenda or develop down-ward accountability. On top of that, political partiesâ involvement in the non-profit organizations is another factor that has compounded the sectorâs lack of public accountability, negative competitiveness, fragmentation, self-serving leadership, and exploitation as a substitute of political arena.Â In NGOsâ opinion, the relationships to various stakeholders range from satisfactory to good especially where the PA, foreign donors, and political factions are concerned. The PAâs hostility towards NGOs stems from suspicion of their political or donor affiliations and NGOs critique of PA policies and performance. However, NGOs accountability flows towards two powerful external stakeholders, the donors and the PA. Consequently, the NGOs are more concerned with upward accountability than with down-ward ones such as to the general public and the non-profit sector as a whole. Â Finally, NGOs accountability dilemma is both a cause and a result of low level of public participation in NGOs affairs due to publicâs lack of trust and the general feeling that NGOs are distant, self-absorbed, and wasting foreign funds on activities lacking sufficient relevance to actual needs.This conclusion based on huge investigation, a combination of qualitative and quantitative methodologies, survey, interview, focus groups in the West Bank, gathering huge data to build a theory from the field.